Realization of Inverse Active Filters Using Single Current Differencing Buffered Amplifier - Paul, T. K.; Roy, S.; Pal, R. R. (Journal of Scientific Research, 2021)
The authors introduce a new single current differencing buffered amplifier (CDBA) based inverse filter configuration. By appropriate selection of admittances, different inverse filter circuits like inverse high-pass (IHP) circuit, inverse low-pass (ILP) circuit, inverse band-reject (IBR) circuit and inverse band-pass (IBP) circuit can be realized from the same configuration. The capacitors used here are grounded/virtually grounded for all the realizations. The performances of the proposed filters have been judged by using CMOS structure of CDBA with TSMC 0.35 µm technology as well as by using the available IC of current feedback operational amplifier (CFOA) i.e. AD844 based CDBA. The simulation results agreed well with the theoretical results. Monte-Carlo simulation has also been performed to check the robustness of the proposed configuration.